Choreodramaturgical Atlas: image constellations as a method of creation in dance (Urdimento: Revista de Estudos em Artes Cênicas, 2023)
The present methodological proposal of choreodramaturgical creation was based on a critical and negative use of the image, having as triggers the poetics and the procedures used by the creator of the Butô dance, Tatsumi Hijikata, and its potential intersections with the universe of the philosophy of the image, mainly with the contributions of thinkers such as Didi-Huberman, Aby Warburg and Georges Bataille. This research began in a post-doctoral period and has gradually gained different material layers as its creative procedures have been updated in different pedagogical and artistic contexts. Therefore, some principles of its conceptual bases are presented here and practical creation experiences are reported in which the Coreodramaturgical Atlas (CDA) has been applied and made more complex in recent years, both in undergraduate and graduate disciplines, and in the process of creating a university artistic research group.
Keywords: image; Buth dance; creative process; aesthetics; montage